﻿Study of phytochemical compounds of Plantago major leaves grown in Kazakhstan - Aknur Turgumbayeva; Kairat Zhakipbekov; Zhanar Shimirova; Sholpan Akhelova; Akerke Amirkhanova; Moldir Koilybayeva; Gulnaz Seitimova; Daniyar Abdambayev (Pensoft Publishers, 2022)
Leaves of Plantago major have been used for centuries to treat diseases relating to skin, digestive organs and blood circulation like wounds, inflammation and hypertension. P. major leaves contain biologically active substance and naturally compounds such as essential oils, minerals and amino acids beside polysaccharides, lipids, caffeic acid and its derivatives, iridoid glycosides, flavonoids and terpenoids. This work carried out an examination of Plantago major leaves in terms of phytochemical composition of methanol extract. The leaves contents in chosen nutrients, specifically amino acids and minerals, are moreover depicted. Gas Chromatography -Mass Spectrometry analysis identified the presence of 31 phytochemical compounds and a total amount of 20 amino acids (essential and nonessential) justifying its use as drugs and biological active supplements and its mineral content showed the presence of 7 essential chemical elements in Plantago major leaves. Nonetheless, additional research into this plant is needed because it has the potential to be used to development of new drugs and biological active supplements.